Pengaruh Hutang Jangka Pendek dan Hutang Jangka Panjang terhadap Laba Bersih pada PT. Siantar Top Tbk Periode 2015 - 2024 - Nadiena Sabhara; Ayu Puspa Lestiyadi (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
The purpose of this study is to determine the effect of short-term debt and long-term debt partially or simultaneously on the company's net profit. The study uses a quantitative method with secondary data in the form of the company's annual financial statements for ten years. The analysis was carried out using multiple linear regression, t-test, F-test, and coefficient of determination, after going through the classical assumption test. Based on the results of the study, it shows that partially short-term debt does not have a significant effect on net profit. This result can be proven by the significance value of the short-term debt variable of 0.232> 0.05 and the t-count value of -1.309 < t-table 1.894. Long-Term Debt partially has a negative and significant effect on Net Profit with a significant value of 0.007> 0.05 and a t-count value of -3.718> t-table 1.894. And simultaneously there is a significant influence of Short-Term Debt and Long-Term Debt on Net Profit because the F count value is 6.981 > F table 4.737 with a significance level of 0.022 < 0.05 the results of this study support the hypothesis that has been obtained that Short-Term Debt and Long-Term Debt have a large influence resulting from the coefficient of determination which is 66.6%. The conclusion of this study confirms that the right debt management structure is the key for PT Siantar Top Tbk in maximizing financial performance.